Stannic Oxide Nanoparticle Regulates Proliferation, Invasion, Apoptosis, and Oxidative Stress of Oral Cancer Cells - Li, Hui; Li, Qiushi; Li, Yingcai; Sang, Xue; Yuan, Haotian; Zheng, Baihong (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: The study is to explore the effect of stannic oxide nanoparticle (SnO2 NP) on proliferation, invasion, apoptosis, and oxidative stress of oral cancer. Methods: The absorption characteristics, X-ray diffraction (XRD) pattern, and transmission electron microscopy (TEM) image of SnO2 NP were measured. The effects of various concentrations of SnO2 NP on the proliferation of oral cancer cells were detected by CCK-8 assay. Furthermore, the cells were divided into control group (DMEM, SnO2 NP 0 μg/mL) and treated group (DMEM, SnO2 NP 100.0 μg/mL), which were used to observe the morphological changes under microscope, measure the cell ability of migration, invasion as well as the apoptosis condition by wound healing, Transwell assay, and flow cytometry, respectively. Moreover, the oxidative stress level was measured by malondialdehyde (MDA) and reactive oxygen species (ROS) detection kits. Finally, the changes in mRNA and protein levels of factors related to cell proliferation, migration, invasion, apoptosis, and oxidative stress were determined by RT-qPCR and Western blot. Results: CCK-8 results indicated that SnO2 NP could inhibit the proliferation of oral cancer cells in a concentration-dependent manner. The results of cell wound healing and Transwell assays demonstrated that SnO2 NP treatment could significantly reduce the cell migration and invasion. The flow cytometry results illustrated that the number of apoptotic cells increased significantly in the SnO2 NP-treated group. The oxidative stress detection showed that SnO2 NP significantly increased the levels of MDA and ROS in oral cancer cells (all P < 0.05). Besides, RT-qPCR and Western blot assays revealed that the concentrations of cyclin-D1 (CCND1), c-myc, matrix metalloproteinase-9 (MMP-9), and MMP-2 in the SnO2 NP-treated group were decreased, while the expression levels of cleaved caspase-3, cleaved caspase-9, and cytochrome C were increased. Conclusion: In the present study, it is found that SnO2 NP could play a cytotoxic role in oral cancer cells by inhibiting cell proliferation, migration, and invasion and inducing oxidative stress and apoptosis, which suggests that SnO2 NP may have various effects on anti-oral cancer. However, a more in-depth study is needed to determine its roles.